High levels of polyandry, but limited evidence for multiple paternity, in wild populations of the western rock lobster (Panulirus cygnus). Issue 9 (10th April 2018) - Loo, Jacqueline; Kennington, Winn Jason; de Lestang, Simon; How, Jason; Evans, Jonathan P.
Abstract: Polyandry, where multiple mating by females results in the temporal and spatial overlap of ejaculates from two or more males, is taxonomically widespread and occurs in varying frequencies within and among species. In decapods (crabs, lobsters, crayfish, and prawns), rates of polyandry are likely to be variable, but the extent to which patterns of multiple paternity reflect multiple mating, and thus are shaped by postmating processes that bias fertilization toward one or a subset of mated males, is unclear. Here, we use microsatellite markers to examine the frequency of multiple mating (the presence of spermatophores from two or more males) and patterns of paternity in wild populations of western rock lobster ( Panulirus cygnus ). Our data confirm that >45% of females had attached spermatophores arising from at least two males (i.e., confirming polyandry), but we found very limited evidence for multiple paternity; among 24 clutches sampled in this study, only two arose from fertilizations by two or more males. Single inferred paternal genotypes accounted for all remaining progeny genotypes in each clutch, including several instances when the mother had been shown to mate with two or more males. These findings highlight the need for further work to understand whether polyandry is adaptive and to uncover the mechanisms underlying postmating paternity biases in this system. Abstract : This study documents patterns of multiple mating (polyandry) and multiple paternity in natural populations of western rock lobster. We report a disconnect between patterns of polyandry and multiple paternity, possibly owing to strong postmating sexual selection in this system.